Strategic Responses of Airlines in Malaysia to the ASEAN Open Skies Policy - Tan, Wei Ghen (2008)
Despite its dependence on global operations, airline industry is excluded from the general agreements on trade in services (GATS). Due to the restrictions imposed by individual countries, the industry was highly regulated. However, pressures for changes have emerged lately due to the economic trend. From bilateral to multilateral agreements, these air services agreements are gradually being substituted by “open skies” arrangement. Most of these arrangements are made through regional or supranational bloc like European Union. The reason behind is to tackle the wider international market. Therefore, the competitive responses in the current scenario are highly defined by the liberalisation processes. Notwithstanding the benefits of having a liberalised market, several researchers have argues that the impacts of international turbulence are momentous. By January 2009, the initial stage of ASEAN Open Skies will take place. This will involves at least fifth freedom rights for airlines in the region to fly within the capital cities of ASEAN. Similar to open skies in other regions, the process will be challenging for many airlines in the ASEAN region. There are many strategies have been implemented by airlines to prepare themselves to a new market structure. Likewise, airlines in Malaysia have been transforming rigorously recently. On one hand, these airlines have to stay competitive in the certain market that have been liberalised, on the other hand, these airlines have to take the initiatives to change for the new market. Consequently, this study is to examine the sensibility of strategic responses by airlines in Malaysia towards the new market structure for open skies – oligopoly. The essay explains why and how airlines in the country response towards the shift in market structure. The study also looks into the challenges and also what are the strategies implemented by these airlines. Finally, this research will examine if the characteristic of the new market structures, oligopoly causes the change in strategies. From the analysis, it shows that the strategic responses of airlines are closely linked to the characteristic of an oligopolistic market. These characteristics have both advantages and also disadvantages to the airlines. The strategic responses of the airlines are therefore, to encounter each of the characteristics. By both overcome the barriers and also taping the new opportunities in the new market structure that are brought by ASEAN Opens Skies, the airlines are also differentiating themselves from other market players.